2016
DOI: 10.3389/fnbeh.2015.00362
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aging and Hippocampus in Time-Place Learning: Link to Episodic-Like Memory?

Abstract: Introduction: With time-place learning (TPL), animals link an event with the spatial location and the time of day (TOD). The what–where–when TPL components make the task putatively episodic-like in nature. Animals use an internal sense of time to master TPL, which is circadian system based. Finding indications for a role of the hippocampus and (early) aging-sensitivity in TPL would strengthen the episodic-like memory nature of the paradigm.Methods: Previously, we used C57Bl/6 mice for our TPL research. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…Interestingly, the peculiar local de-synchronization during Drink adaptation (see above) might indicate that circadian triggering is overridden by some more short-term rhythmicity memory hampered by hippocampal lesions. Whether this could be in line with an eliminated intrahippocampal clock sense as postulated by Mulder et al [41] remains open at present. From a practical point of view, one may note that IntelliCages can be easily programmed to monitor conditioning schemes for analyzing episodic-like memory.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Interestingly, the peculiar local de-synchronization during Drink adaptation (see above) might indicate that circadian triggering is overridden by some more short-term rhythmicity memory hampered by hippocampal lesions. Whether this could be in line with an eliminated intrahippocampal clock sense as postulated by Mulder et al [41] remains open at present. From a practical point of view, one may note that IntelliCages can be easily programmed to monitor conditioning schemes for analyzing episodic-like memory.…”
Section: Discussionmentioning
confidence: 62%
“…Another clear deficit in HIPP mice was found during place as well as reversal learning trials when mice faced the task to obtain water reward only at two given 1 h time periods during conditioning. The task is a circadian-based time-place learning [41] and fits the scheme of episodic-like memory that includes the triple knowledge of what, where and when, which is disturbed in hippocampal lesioned mice [36] . Since the hallmark of (bilateral) destruction of the hippocampus in humans is the loss of episodic memory, there is a wide interest in finding animal models of episodic memory.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, vibrated CD1 mice showed a tendency to improve, which did not reach significant levels. CD1 mice are believed to have a relatively poor functioning hippocampus (Mulder et al, 2016). CD1 mice have a preference for a striatal-driven over a hippocampal-driven strategy to solve spatial tasks; this preference is most likely due to a poor functioning of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility may be that LE rats were 18 months old at the beginning of the 2-platform + board experiment thus might be constrained to mentally less demanding learning strategies. Mulder et al showed that 17-month-old mice-in contrast to 4-month-old counterparts-were unable to learn de novo a time-place discrimination task [15]. However, as 20-month-old LEJ2 rats did show a win-stay strategy in a very similar two choice assay, a more probable explanation may be that the initial strategy of Long-Evans rats in a choice paradigm may be the win-stay one, but in case of its ineffectiveness they change to a simpler one, namely random choice.…”
Section: Discussionmentioning
confidence: 99%
“…TPL can be considered as a particular case of episodic-like memory in which the "what" component is preset for the animal (finding food or an escape route) and this fixed event (episode) should be connected to a particular place-time ("where"-"when") pairing. Interestingly, studies on time-place learning, which have come from comparative behavioral research with an evolutionary approach only recently reached an intersection with the studies on episodic-like memory primarily with a translational approach [14,15]. e current study is part of a bigger project, namely to establish a complex rodent cognitive test battery of high translational value [16].…”
Section: Introductionmentioning
confidence: 99%